Digital exclusion of elderly citizens : Polish experiences based on the project Adult Social Inclusionin a Digital Environment (ASIDE) - Gródek-Szostak, Zofia; Siguencia, Luis Ochoa; Niemczyk, Agata; Seweryn, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The dynamic development of digital technologies and their widespread use in everyday life, especially by younger generations, forces urgent initiatives to counter the digital exclusion of older people. Adult Social Inclusion in and the Digital Environment (ASIDE) has offered activities to support inclusive education and digital skills, raising competences for digital social inclusion of adult social educators and adult social volunteers. The aim of the article is to present the experiences of the ASIDE project in the field of digital inclusion of seniors. Research methods typical of this type of study were used: critical analysis of the literature on the subject, analysis of project documents, analysis of published secondary data.
Keywords: digital exclusion; seniors; ASIDE; project management